CAPN8 involves with exhausted, inflamed, and desert immune microenvironment to influence the metastasis of thyroid cancer - Zhong, Xiang; Xu, Shu; Wang, Quhui; Peng, Long; Wang, Feiran; He, Tianyi; Liu, Changyue; Ni, Sujie; He, Zhixian (Frontiers in Immunology, 2022)
Abstract Background: Thyroid cancer (THCA) is the most prevalent malignant disease of the endocrine system, in which 5-year survival can attain about 95%, but patients with metastasis have a poor prognosis. Very little is known about the role of CAPN8 in the metastasis of THCA. In particular, it is unclear about the effect of CAPN8 on the tumor immune microenvironment (TIME) and immunotherapy response. Material and methods: Multiome datasets and multiple cohorts were acquired for analysis. Firstly, the expression and prognostic value of CAPN8 were explored in public datasets and in vitro tumor tissues. Then, hierarchical clustering analysis was performed to identify the immune subtypes of THCA according to the expression of CAPN8 and the activities of related pathways. Subsequent analyses explored the different patterns of TIME, genetic alteration, DNA replication stress, drug sensitivity, and immunotherapy response among the three immune phenotypes. Finally, five individual cohorts of thyroid cancer were utilized to test the robustness and extrapolation of the three immune clusters. Results: CAPN8 was found to be a significant risk factor for THCA with a markedly elevated level of mRNA and protein in tumor tissues. This potential oncogene could induce the activation of EMT and E2F-targeted pathways. Three subtypes were identified for THCA, including Immune Exhausted, Inflamed, and Immune Desert phenotypes. The exhausted type was characterized by markedly increased expression of inhibitory receptors and infiltration of immune cells but was much more likely to respond to immunotherapy. The immune desert type was resistant to common chemotherapeutics with extensive genomic mutation and copy number variance. Conclusion: The present study firstly explored the role of CAPN8 in the metastasis of THCA from the aspects of TIME. Three immune subtypes were identified with quite different patterns of prognosis, immunotherapy response, and drug sensitivity, providing novel insights for the treatment of THCA and helping understand the cross-talk between CAPN8 and tumor immune microenvironment.